Customs Law = قرار رئيس جمهورية مصر العربية رقم 25 لسنة 2016 بتعديل التعريف الجمركية المنسقة Presidency - Egypt. Presidency (2025)
1. general provision -- 2. customs officials -- 3. customs formalities -- 4. special customs schemes -- 5. customs exemptions -- 6. services charges -- 7. customs contraventions -- 8. smuggling -- 9. selling of goods -- 10 distribution of compensations, fins and the value of confiscation objects.